The school principal : visionary leadership and competent management - Kowalski, Theodore J. (Routledge, 2010)
Over the past two decades, efforts to improve schools have significantly modified role expectations for principals. Today, school-level administrators are expected to be both visionary leaders and competent managers. Based on the conviction that administration is an amalgam of leadership and management, The School Principal emphasizes the need for practitioners to apply conceptual skills to make ""what to do"" decisions, to apply technical skills to make ""how to do"" decisions, and to apply relational skills to engage in democratic decision making. Kowalski frames th.- Resumé vydavatel
Keywords: ředitelé škol -- Spojené státy americké; management školy -- Spojené státy americké; school principals -- United States; school management -- United States; elektronické knihy; příručky; electronic books; handbooks and manuals